How We Read : Tales, Fury, Nothing, Sound - Wilson, Anna (Book collections on Project MUSE., 2019)
"What do we do when we read? Reading can be an act of consumption or an act of creation. Our "work reading" overlaps with our "pleasure reading," and yet these two modes of reading engage with different parts of the self. It is sometimes passive, sometimes active, and can even be an embodied form. The contributors to this volume share their own histories of reading in order to reveal the shared pleasure that lies in this most solitary of acts - which is also, paradoxically, the act of most complete plenitude. Many of the contributors engage in academic writing, and several publish in other genres, including poetry and fiction; some contributors maintain an active online presence. All are engaged with reading's capacity to stimulate and excite as well as to frustrate and confuse. The synergies and tensions of online reading and print reading animate these thirteen contributions, generating a sense of shared community. Together, the authors open their libraries to us. This is how we read."